Effect of Financial Crisis on Firm Performance in Malaysia - Caleb Ee Wan, Cheng; Joanne Shaza, Janang; Sin, Kit Yeng; Nur Nadhira, Baharuddin (HRMARS, 2021)
The purpose of conducting this research is to analyse the relationship between financial crisis and performance of the 14 consumer services listed firms in Bursa Malaysia main market. The period chosen in this research covers from 2015 to 2019, which is 5 years in total. Generally, firms’ value that obtained through the ratio of return on total asset (ROA) serves as the dependent variable in this research. Two independent variables involve in this research are debt ratio and debt to equity ratio.